2010
DOI: 10.3342/ceo.2010.3.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Otolaryngologic Diseases in South Korea: Data from the Korea National Health and Nutrition Examination Survey 2008

Abstract: ObjectivesThe aims of this study were to evaluate the prevalence of otolaryngologic diseases in Korea.MethodsWe obtained data from the 2008 Korea National Health and Nutrition Examination Surveys (KNHANES), which were cross-sectional surveys of the civilian, non-institutionalized population of South Korea (n=4,930). A field survey team that included an otolaryngologist, nurses, and interviewers moved with a mobile examination unit and performed otolaryngologic interviews and physical examinations.ResultsThe pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 42 publications
3
63
2
1
Order By: Relevance
“…This result was in accordance with previous findings from a population-based study in South Korea, although AR was diagnosed only by their symptoms without allergen tests. 7 Other studies have shown that the most prevalent type of AR is persistent moderate/severe AR. 24,25 We attribute this difference to the fact that their subjects were recruited from hospital visit- genders (test for trend, p ϭ 0.11 in men and p ϭ 0.13 in women).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was in accordance with previous findings from a population-based study in South Korea, although AR was diagnosed only by their symptoms without allergen tests. 7 Other studies have shown that the most prevalent type of AR is persistent moderate/severe AR. 24,25 We attribute this difference to the fact that their subjects were recruited from hospital visit- genders (test for trend, p ϭ 0.11 in men and p ϭ 0.13 in women).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a nationwide study reported that its prevalence was 28.01% in 2008, diagnosed only by nasal symptoms without an allergen test. 7 The Korean NHANES (KNHANES), which is a government-driven survey of the Korea Center for Disease Control and Prevention, has been conducted since 1998. The Korean Society of OtorhinolaryngologyHead and Neck Surgery (KORL) participated in this project and interviews and examinations were performed by trained ear, nose, and throat (ENT) residents.…”
mentioning
confidence: 99%
“…An otoscopic examination was then conducted with a 4-mm 0-degree rigid endoscope attached to a CCD camera for all participants aged 4 years or older to determine the prevalence of tympanic membrane (TM) perforation, cholesteatomatous condition including retraction pocket, and otitis media with effusion. Then, the hearing threshold and vestibular function were evaluated in participants older than 12 and 40 years, respectively, as previously described (9).…”
Section: Surveymentioning
confidence: 99%
“…During the otolaryngologic interview and examination, participants who were aged 19 years were surveyed for any history of voice disorders, and vocal fold examinations using rigid telescopic laryngoscopy were subsequently conducted on those participants. 1, 2 The prevalence of voice disorders in the United States was reported to be 6.6% in 2005 3 ; voice problems are more common in women than in men, and the prevalence increases with age. 4 It has been reported that 3-9% of Americans have experienced voice problems, 5 which can lead to unemployment secondary to voice problems as well as medical bills.…”
Section: Introductionmentioning
confidence: 99%